Nephroprotective Effect of Fennel (Foeniculum vulgare) Seeds and Their Sprouts on CCl4-Induced Nephrotoxicity and Oxidative Stress in Rats - Hassan Barakat; Ibrahim Ali Alkabeer; Sami A. Althwab; Hani A. Alfheeaid; Raghad M. Alhomaid; Mona S. Almujaydil; Raya S. A. Almuziree; Taqwa Bushnaq; Ahmed Mohamed (MDPI AG, 2023)
Functional and nutritional characteristics of seed sprouts and their association with oxidative stress-related disorders have recently become a focus of scientific investigations. The biological activities of fennel seeds (FS) and fennel seed sprouts (FSS) were investigated in vitro and in vivo. The total phenolic content (TPC), total flavonoids (TF), total flavonols (TFF), and antioxidant activity (AOA) of FS and FSS were examined. HPLC and GC-MS analyses for FS and FSS were carried out. Consequently, the nephroprotective and antioxidative stress potential of FS and FSS extracts at 300 and 600 mg kg−1 on CCl4-induced nephrotoxicity and oxidative stress in rats was investigated. In this context, kidney relative weight, blood glucose level (BGL), lipid profile, kidney function (T. protein, albumin, globulin, creatinine, urea, and blood urea nitrogen (BUN)), and oxidative stress biomarkers (GSH, CAT, MDA, and SOD) in the rat's blood as well as the histopathological alteration in kidney tissues were examined. Results indicated that the sprouting process of FS significantly improved TPC, TF, TFL, and AOA in vitro. HPLC identified nineteen compounds of phenolic acids and their derivatives in FS. Thirteen phenolic compounds in FS and FSS were identified, the highest of which was vanillic acid. Six flavonoids were also identified with a predominance of kaempferol. GC-MS indicated that the trans-anethole (1-methoxy-4-[(E)-prop-1-enyl]benzene) component was predominant in FS and FSS, significantly increasing after sprouting. In in vivo examination, administering FS and FSS extracts ameliorated the BGL, triglycerides (TG), total cholesterol (CHO), and their derivative levels compared to CCl4-intoxicated rats. A notable improvement in FS and FSS with 600 mg kg−1 compared to 300 mg kg−1 was observed. A dose of 600 mg FSS kg−1 reduced the TG, CHO, and LDL-C and increased HDL-C levels by 32.04, 24.62, 63.00, and 67.17% compared to G2, respectively. The atherogenic index (AI) was significantly improved with 600 mg kg−1 of FSS extracts. FS and FSS improved kidney function, reduced malondialdehyde (MDA), and restored the activity of reduced glutathione (GSH), superoxide dismutase (SOD), and catalase (CAT). Both FS and FSS extracts attenuated the histopathological alteration in CCl4-treated rats. Interestingly, FSS extract presented better efficiency as a nephroprotection agent than FS extract. In conclusion, FSS can potentially restore oxidative stability and improve kidney function after acute CCl4 kidney injury better than FS. Therefore, FS and FSS extracts might be used for their promising nephroprotective potential and to help prevent diseases related to oxidative stress. Further research on their application in humans is highly recommended.